PLA2G12B Mediates Arachidonic Acid Metabolism through Activation of the NF-κB Pathway to Promote Membrane Nephropathy - Linlin Fu; Jinliang Ping; Fei Guo; Jiafeng Song; Mingjun Luo; Lijing Chen (Karger Publishers, 2023)
Introduction: The disruption of podocyte structure and function are the main pathological mechanism of membranous nephropathy (MN). Phospholipases A2, Group XII B (PLA2G12B) was reported involved in the regulation of MN by interfering with arachidonic acid (AA) metabolism, but there is a lack of sufficient evidence. In this study, we investigated the role and molecular mechanism of PLA2G12B in MN. Methods: C57BL/6 mice were used to establish MN model to extract primary podocytes, then divided into control, model, si-phospholipases A2 receptor (PLA2R), PLA2G12B, PLA2G12B + si-PLA2R, PLA2G12B + nuclear factor kappa-B (NF-κB) inhibitor, PLA2G12B + NF-κB inhibitor + si-PLA2R groups. Hematoxylin-eosin staining and immunofluorescence were used to detect kidney histological arrangement, serum levels of cholesterol-related indices, and AA. Genes and proteins associated with metabolism and inflammatory factors were detected by quantitative real-time PCR and Western blot. Results: The results revealed that AA metabolites were activated in the MN model mice, and the expression of PLA2G12B and NF-κB pathway levels were elevated. Besides, cellular experiments demonstrated that prostaglandin I2 (PGI2), thromboxane A2 (TXA2), leukotriene B4 (LTB4), and NF-κB pathway were significantly increased in the PLA2G12B group. Also, PLA2G12B promotes apoptosis and suppresses cell activity in podocytes, and these effects could be antagonized by NF-κB inhibitors. Furthermore, with the inference of si-PLA2R, the NF-κB inhibitors' effects were reversed. Conclusion: Promotional effects of PLA2G12B in primary MN are associated with the regulation of AA metabolism and NF-κB pathway.